Corrosion Inhibition Properties of Telfaira occidentalis Leaf Extract on Aluminium in 1.5M HCl Medium - F. A., Dawodu; E. F., Sodiya (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Corrosion inhibition of aluminium by leaf extract Telfaira occidentalis in 1.5 M HCl was investigated using the gasometric technique at 28oC. Results obtained showed that the extract displayed high inhibition efficiency against corrosion of aluminium in 1.5 M HCl solution. The extract displayed nearly the inhibition efficiencies at concentration range 10 – 50% dilution of the extract. The corrosion inhibition mechanism followed Langmuir adsorption isotherm at the studied temperature. This suggests the extract constituent chemisorbed on the aluminium surface forming a protective film minimising direct contact with the corrodent.